The complete nucleotide sequence of the tryptophan operon of Escherichia coli. - Yanofsky, C (1981)
The tryptophan (trp) operon of Escherichia coli has become the basic reference structure for studies on tryptophan metabolism. Within the past five years the application of recombinant DNA and sequencing methodologies has permitted the characterization of the structural and functional elements in this gene cluster at the molecular level. In this summary report we present the complete nucleotide sequence for the five structural genes of the trp operon of E. coli together with the internal and flanking regions of regulatory information.